SISTEM MONITORING DETEKSI CUACA BERBASIS INTERNET OF THINGS (IoT) - Raden Kania; Waliadi Gunawan; Tifani Intan Solihati; Nur Hidayanti; Agus Miftach (Jurnal Sistem Informasi dan Informatika (Simika), 2024)
Abstract Banten Jaya University has a website https://www.unbaja.ac.id which was created in 2018 to make it easier for students to access academic information. Although this website has grown rapidly over time, it does not yet provide campus weather information. Some official weather sites only cover sub districts, not taking into account campus locations. Therefore, this research develops an Internet of Things (IoT) based weather monitoring system using nodemcu and temperature, humidity and weather intensity data. This research uses the Waterfall Method and produces an effective tool that can monitor the weather situation on the Banten Jaya University campus using the DHT 11 sensor, LDR sensor and Raindrop sensor. This research is the first step in developing a weather monitoring system on campus.